2012
DOI: 10.1002/pca.2400
|View full text |Cite
|
Sign up to set email alerts
|

Dehydropyrrolizidine Alkaloids in Two Cryptantha Species: Including Two New Open Chain Diesters One of Which is Amphoteric

Abstract: The retronecine-based alkaloids detected in both Cryptantha species herein investigated aligns them within the Krynitzkia subgenus. The dehydropyrrolizidine alkaloids detected are expected to be toxic but the low levels in the plants potentially mitigate the risk. The identification of the amphoteric echiuplatine provides a cautionary note with respect to the analysis of total dehydropyrrolizidine alkaloid content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…Accordingly, the proton resonances noted for echivulgarine were all consistent with the trends noted 30 for a syn relationship between H-7 and H-8, although the signals for H 2 -6 to H-8 resonate approximately 0.2 ppm downfield of those reported previously. 30 Such a syn relationship would result in the 7R*, 8R* relative configuration as previously assumed. This proposed relative configuration was supported by observation of multiple through-space interactions via a two-dimensional NOESY experiment (Figure 3).…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 88%
“…Accordingly, the proton resonances noted for echivulgarine were all consistent with the trends noted 30 for a syn relationship between H-7 and H-8, although the signals for H 2 -6 to H-8 resonate approximately 0.2 ppm downfield of those reported previously. 30 Such a syn relationship would result in the 7R*, 8R* relative configuration as previously assumed. This proposed relative configuration was supported by observation of multiple through-space interactions via a two-dimensional NOESY experiment (Figure 3).…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 88%
“…Since it has been previously shown that 2D NOESY interactions between H7 and H8 are an unreliable indicator of the relative configuration of these protons in some dehydroPAs (Colegate et al, 2013), an attempt was made to demonstrate the heliotridine or retronecine configuration of alkaloid 10 using a 1D GOESY NMR experiment. However, using heliotrine and lycopsamine as model heliotridine and retronecine monoesters respectively, a GOESY interaction was observed for both.…”
Section: Resultsmentioning
confidence: 99%
“…(2008) and applied to the necine base determination of the open chain diester dehydroPA cryptanthine (Colegate et al, 2013), LiAlH 4 solution (200 μL) was added to each sample vial and left to stand at room temperature for 2 h. Dichloromethane (1 mL) was added to each vial, causing very slight effervescence with the LiAlH 4 mixtures. Cautiously, 1 drop at a time, an aqueous solution of sodium hydroxide (10% w/v) was added resulting in vigorous effervescence and formation of a glutinous white solid.…”
Section: Methodsmentioning
confidence: 99%
“…MCT concentration of the seeds was determined by HPLC-ESIMS analysis of methanolic extracts using authentic MCT (crotaline; Sigma-Aldrich, USA) as the calibration standard (COLEGATE et al, 2012a(COLEGATE et al, , 2012b.…”
Section: Methodsmentioning
confidence: 99%